Reducción de costos para identificar perfiles de usuarios en el sector retail a través de tecnologías de conectividad inalámbrica - Redhead Llanos, Monica Eliza (2021)
Wireless technology can be used to enable a marketing channel, allowing the enhancement of an online service that will be deployed in the commercial premises of customers in the retail sector. The objective of this work has been to reduce operating costs for the marketing area through the capture of location information or physical location and movement in the final customer's store, without the need for them to register on the wireless network. The marketing area through this information could support the process of the interested key user, in aspects related to the products and services that are offered. This solution will then be deployed as a service, which will be enabled through a web page for the generation of reports in accordance with the client's requirements, relying on the processing of the information that will be provided in rental mode over the cloud. Through this service, important savings can be obtained, since it would not be necessary to contract external consultancy for the process of gathering information, processing it, or analyzing it.